LEVEL OF PHYSICAL ACTIVITY AND OBESITY IN ADOLESCENTS OF SECONDARY EDUCATION (Fiep Bulletin - online, 2015)
Obesity in children and adolescents has been spreading increasingly in recent decades, this due to the increase in technology and sedentary lifestyle, their appearance at this age becomes a disturbing fact because the disease can remain throughout adulthood and triggers other health problems, decreasing the quality of life of the individual. Therefore, the aim of this study was to examine the relationship between physical activity and obesity in high school students in the city of Quatiguá - PR. For data collection anthropometric measures of body mass and height in order to get the BMI of students, and measures of waist and hip circumference in order to establish the WHR were measured; the Baecke questionnaire was used to assess levels of physical activity among individuals. Statistical analysis was used Bioestat 5.4 software for testing the normality of Shapiro-Wilk, and consequently the criterion ANOVA test for parametric data was used, whereas non-parametric data were analyzed using the Kruskal-Wallis test. Adopting significance to the value of p?0.05. The results showed that in this population with respect to characteristic anthropometric second WHO (2009), has been a normality of all series examined in relation to the BMI. Ever, with respect to the Baecke questionnaire revealed that the equalization was notorious manifestations of this practice on a regular basis in all series analyzed, both for the work index, as for leisure and sport.
Keywords: Obesity; Adolescents; physical activity